Aerial and Ground Surveys as a Tool in Game Selection for Domestication: The Kainji Experience - Abere, Sodienye A.; Oguzor, Nkasiobi S. (Richtmann Publishing, 2012)
IntroductionThere are several tools used in game selection for domestication social acceptance, adaptability and gameinventory to mention but a few. In this paper we must devote most of our discussion on game inventory,game social stress condition both of which are most related to survey of animal population. If there be nogame inventory, how do we know the available lot of game to be selected from.